2016
DOI: 10.1037/cbs0000058
|View full text |Cite
|
Sign up to set email alerts
|

Renewed promise for positive cross-group contact: The role of supportive contact in empowering collective action.

Abstract: Positive cross-group contact can undermine disadvantaged group members' collective action engagement. However, we hypothesized that positive cross-group contact in which an advantaged group member explicitly communicates opposition to inequality between groups ("supportive contact") would not undermine collective action and would be empowering for disadvantaged group members. Study 1 focused on cross-group contact between international students and domestic students at an Australian university. Study 2 focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 46 publications
3
58
0
Order By: Relevance
“…We empirically demonstrated that dominant group allies exhibit characteristics of both affirmation and informed action (Brown & Ostrove, ) in a way that distinguishes them from nonnominated white people and from nominated white friends. Using a different construct to understand our findings, allies appear to demonstrate “supportive contact”—they are friendly, respectful, and caring toward nondominant group members, and also oppose inequality or support efforts toward social change (Droogendyk et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…We empirically demonstrated that dominant group allies exhibit characteristics of both affirmation and informed action (Brown & Ostrove, ) in a way that distinguishes them from nonnominated white people and from nominated white friends. Using a different construct to understand our findings, allies appear to demonstrate “supportive contact”—they are friendly, respectful, and caring toward nondominant group members, and also oppose inequality or support efforts toward social change (Droogendyk et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Other recent work on allies (Droogendyk et al, ) highlights the importance of attending to the challenges associated with ally relationships: although advantaged group allies' activism may serve to empower some disadvantaged group members, it can also offer dependency‐oriented help (see Nadler & Halabi, ), co‐opt the identities of disadvantaged group members, or take over the goals and agenda of the disadvantaged group. Droogendyk et al's work underscores the importance of allies attending to their own privileged status and position; we agree that attention to identity, positionality, and privilege among allies is critical, and our work offers empirical evidence that white allies who were nominated by people of color do indeed exhibit higher levels of awareness of privilege than white people who were nominated by people of color as friends.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to the disadvantaged who speak up for themselves, advantaged group members who oppose unequal power relations are more persuasive to the general audience (e.g., Czopp & Monteith, ) and have greater assets to act upon their attitudes (Iyer & Leach, ). Moreover, as long as they explicitly communicate their opposition to inequality, dominant group allies may inspire engagement of low‐status group members (Droogendyk, Louis, & Wright, ; Droogendyk et al, ; Techakesari, Droogendyk, Wright, Louis, & Barlow, ; but see Saguy, Tausch, Dovidio, & Pratto, ). Therefore, it is important to identify the barriers that discourage high‐status group members from acting in solidarity with the disadvantaged (Becker & Tausch, ).…”
Section: Discussionmentioning
confidence: 99%